(3MdI GdCYjGf Ydi YeOI GdHjGfs - (3MSjf Hf Ydj Hf WdMI GdQLQGLi GdThTGhi GdSedGdis; (3CHh RjO YHO GdQMfe CHh ZdSj GdeZQHj GdeGdcj,J (B807 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ MSjf Hf Ydi Hf WdMI GdQLQGLi GdThTGhi dWa Gddg Hg hHYO agPG cJGH SejJg MdI GdCYjGf Ydi YeOI GdHjGf hSfHZi Cf jbOe GdcdGe gGgfG ai YTQjf aUdkG CMOgeG Ydi cJH GdeUMa s
(3BNQgG (B:s
(3Ch MGd ebOeI CUdg GdfYJ Je GdcJGH GdeSei Mdi GdGYjGf Ydi YeOi GdHjGf hGdMeO ddg hGdKfGA hGdTcQ ddg JYGdi ceG jfHZi GdTcQ dg hGdUdGI Ydi eMeO ceG jfHZi GdUdGI Ydjg hGdUdGg Ydi Bd eMeO ceG jfHZi Cf jUdi Ydjge hQVi Gddg Yf CUMGH eMeO ceG jfHZs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ YfGhjfgG HGdMHQ GdCMeQ s
(3hQbI GdYfhGf YdjgG JUhjHGJ hEXgGQ GdcdeGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdJaSjQ hYdhe GdbQBfs